A replicable acoustic measure of lenition and the nature of variability in Gurindji stops. Issue 1 (22nd August 2017) - Ennever, Thomas; Meakins, Felicity; Round, Erich R.
Abstract : An automated method is presented for the commensurable, reproducible measurement of duration and lenition of segment types ranging from fully occluded stops to highly lenited variants, in acoustic data. The method is motivated with respect to the relationship between acoustic and articulatory phonetics and, through subsequent evaluation, is argued to correspond well to articulation. It is then applied to the phonemic stops of casual speech in Gurindji (Pama-Nyungan, Australia) to investigate the nature of their articulatory targets. The degree of stop lenition is found to vary widely. Contrary to expectations, no evidence is found of a positive effect on lenition due to word-medial (relative to word-initial) position, beyond that attributable to duration; nor do non-coronals lenite more than their apical counterparts, which freely lenite along a continuum towards taps. No significant effect is found of preceding or following vocalic environment. Taken together, the observed lenition, duration, and peak intensity velocities are argued to be inconsistent with a single, fully-occluded articulatory 'stop' target which is undershot at short durations, rather targets can be understood to span a range or 'window' of values in the sense of Keating (1990 ), from fully-occluded stop-like targets to more approximant-like targets. It is an open question to what degree the patterns found in Gurindji are language particular, or can be related to the organization of obstruent systems in Australian languages more broadly. Precisely comparable studies of additional languages will be especially valuable in addressing these questions and others, and are possible using the method we introduce.